IMPLEMENTASI PERDA NOMOR 13 TAHUN 2019 TENTANG BADAN PERMUSYAWARATAN DESA DI KABUPATEN SUMEDANG - Dadan Setia Nugraha (JRPA - Journal of Regional Public Administration, 2023)
The focus of this research is due to the not yet good implementation process of Regional Regulation Number 13 of 2019 concerning the Village Consultative Body in Sumedang Regency. This study aims to find out and analyze the Implementation of Regional Regulation Number 13 of 2019, the inhibiting factors for the Implementation of Regional Regulation Number 13 of 2019 and the efforts that have been made by the Community and Village Empowerment Service in implementing Regional Regulation Number 13 of 2019 concerning the Consultative Council and Villages of Sumedang Regency. The method used in the preparation of this research is a qualitative. The sample technique used is purposive sampling. The research informants were: the Head, and Pemdes Policy Analyst at PMD Service, Sumedang Regency, totaling 2 people. Meanwhile, in analyzing the data, the Miles and Huberman models were used with the steps: data reduction, data presentation, drawing conclusions and triangulation techniques. Based on the results of research on the implementation of Regional Regulation No. 13 of 2019 concerning Village Consultative Councils at the Community and Village Empowerment Service of Sumedang Regency, it can be seen from each dimension and indicator have been well implemented but not optimal. It is hoped that with the Implementation of Regional Regulation Number 13 of 2019 that in implementing a policy there must be clarity of policy standards and objectives, fulfillment of needed resources, strong coordination both between individuals in an organization and with other agencies, good implementer position, and environmental conditions that affects it.